2017
DOI: 10.1007/s10750-017-3186-3
|View full text |Cite
|
Sign up to set email alerts
|

Sepiolid paralarval diversity in a regional upwelling area of the NE Atlantic

Abstract: Sepiolid paralarvae are poorly studied, at least in part, because of the difficulty of accurate identification using morphological analysis. To unravel the biodiversity of sepiolid paralarvae collected in the Ría de Vigo during the upwelling season (2012)(2013)(2014), and to overcome the difficulties of traditional identification, sepiolid paralarvae were identified by amplifying the barcoding gene cytochrome c oxidase subunit I (COI). In addition, morphometric analysis (Generalised Lineal Models, GLM and Disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…In the present study, we observed that D. pleii had a high haplotype and nucleotide diversity, according to the values proposed by Goodall-Copestake et al (2012), with no population structuring. The haplotype network presented a star shape also found in this species (Sales et al, 2017) and other loliginid species (Olmos-Peŕez et al, 2018;Roura et al, 2019;Garcıá-Mayoral et al, 2020) where many unique haplotypes radiate from few common haplotypes. This pattern indicates high gene flow, which suggests that there are no barriers preventing the spread of this species along and across the YS.…”
Section: Pleii Genetic Structuresupporting
confidence: 65%
See 1 more Smart Citation
“…In the present study, we observed that D. pleii had a high haplotype and nucleotide diversity, according to the values proposed by Goodall-Copestake et al (2012), with no population structuring. The haplotype network presented a star shape also found in this species (Sales et al, 2017) and other loliginid species (Olmos-Peŕez et al, 2018;Roura et al, 2019;Garcıá-Mayoral et al, 2020) where many unique haplotypes radiate from few common haplotypes. This pattern indicates high gene flow, which suggests that there are no barriers preventing the spread of this species along and across the YS.…”
Section: Pleii Genetic Structuresupporting
confidence: 65%
“…This is also true for the southeastern Gulf of Mexico (SGoM), where the loliginid squid fishery is mostly obtained incidentally as a by-catch from the shrimp and sardine fisheries, while catches per unit of effort are not recorded most of the time (Solıś-Ramıŕez et al, 1998; Comisio ́n Nacional de Pesca (CONAPESCA), 2018). The lack of reliable information limits the evaluation of the stocks and impedes the establishment of local management and/or conservation strategies (Ward, 2000;Olmos-Peŕez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To address such problems for sepiolid species off western Spain, Olmos-Pérez et al (2017) combined the sequencing of the mitochondrial cytochrome c oxidase subunit I (COI) barcoding gene with simple morphometric measurements and morphological observations. Using statistical correlations, they were able to identify distinguishing morphological features with reasonable accuracy among the three consistently dominant sepiolid species.…”
mentioning
confidence: 99%